Rukun perkawinan perspektif 4 mazhab: tinjauan kitab rohmatul ummah - Ikhsan, Muhamad Khoiron (Maliki Interdisciplinary Journal, 2026)
This study discusses the differences in views among the four major Islamic schools of thought, namely Hanafi, Maliki, Shafi’i, and Hanbali, regarding the pillars of marriage with reference to the book Rohmatul Ummah fi Ikhtilafi al-Ummah. The focus of the study includes the position of the bride and groom, the guardian, the witnesses, and the shigat ijab qabul in determining the validity of the marriage contract. Using a qualitative method based on literature study, this research describes the similarities and differences in the opinions of the scholars and their implications for the practice of Islamic family law. The results show that the Shafi’i, Maliki, and Hanbali schools of thought agree that the pillars of marriage include the prospective husband and wife, the guardian, two witnesses, and the ijab qabul, while the Hanafi school of thought only considers the ijab qabul as the main pillar and places other elements as conditions for validity. These findings confirm that the understanding of the pillars of marriage is not only theoretical but also has practical implications in determining the validity of marriage in various Islamic social contexts. This study is expected to enrich the knowledge of fiqh al-usrah and contribute to the harmonization of Islamic legal thought amid the diversity of schools of thought.